2013
DOI: 10.1063/1.4801893
|View full text |Cite
|
Sign up to set email alerts
|

Incipient piezoelectrics and electrostriction behavior in Sn-doped Bi1/2(Na0.82K0.18)1/2TiO3 lead-free ceramics

Abstract: Articles you may be interested inElectric-field-temperature phase diagram of the ferroelectric relaxor system (1−x)Bi1/2Na1/2TiO3−xBaTiO3 doped with manganese J. Appl. Phys. 115, 194104 (2014) Relaxorlike dielectric properties and history-dependent effects in the lead-free K 0.5 Na 0. Dielectric, ferroelectric, piezoelectric, and strain properties of lead-free Sn-doped Bi 1/2 (Na 0.82 K 0.18 ) 1/2 TiO 3 (BNKT) were investigated. A crossover from a nonergodic relaxor to an ergodic relaxor state at room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(57 citation statements)
references
References 39 publications
4
52
1
Order By: Relevance
“…Interestingly, despite the results showing the electric-field-induced evolution of mixed phase compositions between BNT-5BT and BNT-11BT, optimal properties were still observed at around BNT-7BT as was reported by Takenaka et al 6 In addition, Ma et al 15 have reported electric-field-induced creation/modification of MPB in this material system by in situ TEM. The unusual phase transformation behaviour of BNT-100xBT compositions is of interest as it's been shown to provide a mechanism to so-called "giant" strain property or incipient piezoelectricity [16][17][18][19] in related BNTbased compositions.…”
mentioning
confidence: 99%
“…Interestingly, despite the results showing the electric-field-induced evolution of mixed phase compositions between BNT-5BT and BNT-11BT, optimal properties were still observed at around BNT-7BT as was reported by Takenaka et al 6 In addition, Ma et al 15 have reported electric-field-induced creation/modification of MPB in this material system by in situ TEM. The unusual phase transformation behaviour of BNT-100xBT compositions is of interest as it's been shown to provide a mechanism to so-called "giant" strain property or incipient piezoelectricity [16][17][18][19] in related BNTbased compositions.…”
mentioning
confidence: 99%
“…5. There are two distinctive dielectric anomalies evident in dielectric constant and loss for both unpoled and poled ceramics: a shoulder at a lower temperature with a strong frequency dispersion and frequency-insensitive peaks at a higher temperature, which indicates that the BNT-BKT-5ST textured ceramics exhibits relaxor characteristics [29,30]. Jo et al [23,30] proposed that the origin of the commonly observed two dielectric anomalies in BNT-based systems can be understood as a convolution of three distinctive processes as follows: a dielectric relaxation at low temperature contributed by coexisting PNRs of different symmetries, a diffuse phase transition at intermediate temperature derived from low symmetry PNRs to higher symmetry ones, and an additional dielectric relaxation process at high temperature originated from the remaining high symmetry PNRs.…”
Section: Resultsmentioning
confidence: 95%
“…The random BNT-BKT and BNT-BKT-5ST textured ceramics show a typical butterfly shape with a large negative strain related to domain back switching, which is typical for ferroelectric materials. Note that, with the addition of BT template particles, the bipolar strain curves exhibit a drastic deviation from the typical butterfly shaped strain hysteresis to a sprout-shaped one, indicating the destabilization of ferroelectricity at zero field [3,29,30]. Instead, a pronounced reduction of the negative strain from 0.1% for random BNT-BKT to 0.003% for textured BNT-BKT-5BT was observed accompanied by a large strain of 0.32% under a relatively low electric field of 45 kV/cm, suggesting that a small negative strain promotes the potential for a material to display large strain response due to the appearance of the weakly polar phase [24].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is highly comparable to that of lead-based single crystals (Figures 1d and e). 4,21,[25][26][27][28][29][30] Figure 2a presents a representative microstructure of an as-sintered RTGG specimen demonstrating a high degree of texture. It is interesting to see that every grain, without exception, shows clear ferroelectric domain contrast.…”
Section: Resultsmentioning
confidence: 99%